The dialogic performance in Arabic language curricula between diagnosis and treatment - Bani Yasin, Mohammed Fawzi (Arab Journal for Sciences and Research Publishing, 2016)
This study aims to describe and investigate the extent to which Arabic curricula in Jordan (from the First grade to the Tenth grade) achieved the dialogic performance in Arabic Language curricula. To achieve this, the researcher uses the descriptive approach by recording and gathering the educational situations that are used to achieve and fulfill this goal according to the criteria of the dialogic performance in form and content. The study demonstrates that Arabic curriculum with all its elements of aims, content, activities and evaluation include and concentrate on the treatments that improve the dialogic performance. The study comes up with introducing a suggested educational model to improve the level of the dialogic performance and with some recommendations.
Keywords: Arabic language curricula; conversational performance